Setting up Indus Telemetry for canal flow monitoring: a learning experience - Bhatti, Muhammad Tousif; Ashraf, Muhammad; Hussain, Kashif; Khattak, K.; Yasir, M.; Malik, M. A. (International Water Management Institute, 2026)
Indus Telemetry was launched in 2017 as a research-for-development initiative in Pakistan, led by the International Water Management Institute (IWMI), in collaboration with the Pakistan Council of Research in Water Resources (PCRWR) and provincial irrigation departments. Its purpose was to develop a transparent, automated system for monitoring canal flows and supporting surface water accounting across the Indus Basin Irrigation System in Pakistan. The project concluded in 2025 with the successful transfer of the system to a provincial irrigation department, marking a sustainable handover of both technology and operational capacity.